Notice of Joint Meeting Between the Camarillo and Oxnard Airport Authorities March 8, 2001 (2001)
The agenda for a meeting on March 8, 2001 between the Camarillo Airport Authority and the Oxnard Airport Authority. Discusses the development of a fence around Camarillo Airport, developments in the low-flying aircraft monitoring system, a request for a grant amendment, and a review of proposed school sites.